Critical narrative as a framework for professional border crossing in early childhood. (September 2017) - Brown, Alice; Grigg, John
Early childhood educators are regularly confronted by dominant discourses (e.g. ensuring children are prepared for school) and the politics and pedagogy that are embedded in their practice and early childhood contexts. These discourses impact on ways of thinking and engaging with others, and professional behaviour, as well as shaping curriculum documents and policy. Engaging in a process of critical reflection from a post-structuralist perspective helps to disrupt deeply seated beliefs and assumptions, resist tensions of power and regulation, and increase feelings of agency. This article offers educators a rationale for adopting such an approach, and presents a lens with which to view alternative discourses and for thinking otherwise. The authors introduce a framework which includes a range of strategies that educators may choose to add to their tool kit to unpack and make sense of their experiences. An exemplar is offered to showcase engagement with these tools, including the use of critical narrative. Employing strategies and practices such as those outlined in this article opens possibilities to feel more empowered as early childhood educators, and be better equipped to give voice to their thoughts, feelings of hope and potential as active agents.